From Spirituality to Social Interaction: Symbolic Communication of Tariqah Qadiriyah wa Naqsyabandiyah Khathibiyah Sambas Adherents - Sabari Sabari; Ahmad Sayyid Aulawi (Nalar: Jurnal Peradaban dan Pemikiran Islam)
This article aims to analyze the symbolic communication of adherents of the Tariqah Qadiriyah wa Naqsyabandiyah Khathibiyah in Sambas. The paradigm in this study is interpretive with a sociological approach. The method used is phenomenology. Data collection was conducted from March to June 2023. Data were collected by conducting observations, interviews, and documentation. The informants in this study totaled 13 people using the snowball sampling technique. The data obtained were analyzed using qualitative analysis procedures: data reduction, data display, and conclusion. This study found that the symbolic communication of adherents of the Tariqah Qadiriyah wa Naqsabandiyah Khathibiyah Sambas is not formed by itself but through an interrelated process between the meaning of the adherents of the tariqah, the formation of self-concept, and represented in communication patterns. The process is initiated from the adherent's interpretation of the doctrines of the tariqah to form the adherent's self-concept. Then, the self-concept has implications for adherents' behavior and social interactions. Based on the findings, it is concluded that the symbolic communication that occurs among adherents is an implication and symbolic representation of the doctrines and spirituality experiences of adherents of the Tariqah Qadiriyah wa Naqsabandiyah Khathibiyah Sambas.